Analisis Penggunaan SIMKAH di Kantor Urusan Agama Kecamatan Pino Raya Bengkulu Selatan - Vina Gracenia; Titi Darmi (JPSI (Journal of Public Sector Innovations), 2022)
This study aims to analyze the use of Simkah at KUA Pino Raya District. The development of information technology has made the KUA of Pino Raya District apply Simkah to organize marriage registration and improve services for community satisfaction. This research uses a descriptive qualitative method. Data collection techniques using observation, interviews and documentation. While the data analysis technique uses interactive model analysis, namely data collection, data condensation, data presentation, and drawing conclusions. The results showed that the use of Simkah at the KUA in Pino Raya District made it easy to input data, speeding up access, even though the online registration process was not going well. However, Simkah has provided security guarantees and responses according to user needs. Simkah has provided satisfaction to the users. Simkah provides many advantages and benefits for KUA Pino Raya District.